Generating evidence for planning eye care service delivery in an urban underprivileged population setting in Pune, Western India - Kulkarni, Sucheta (BMJ Open Ophthalmol, 2019)
PURPOSE: To estimate prevalence of blindness, diabetic retinopathy and causes of blindness through rapid assessment of avoidable blindness (RAAB) survey in Pune, India to develop an evidence base for planning urban eye care services. METHODS: ‘Rapid assessment of avoidable blindness and diabetic retinopathy’ methodology was used. Compact segment sampling was used in each of the 60 selected electoral wards identified through cluster selection module of the RAAB software using probability proportionate to size method. Persons >50 years of age were enumerated from selected segments to achieve cumulative target of 60/day by two teams. Participants underwent presenting and pinhole visual acuity (VA) testing in each eye. A torch light examination and direct ophthalmoscopy established cause of visual impairment/blindness if present. Data were entered into and analysed using RAAB software. RESULTS: The response rate was 89.5% (3221/3600), and 55.3% were women. Results of only RAAB module are presented in this paper. Age-standardised and sex-standardised prevalence of blindness was 1.3% (95% CI 0.9 to 1.8). Cataract was the most common cause of blindness (45.7%) followed by overall posterior segment disorders (39.1%). Cataract surgical outcome was good (VA>6/18) or very good (VA>6/12) in 805/1190 (67.6%) cases. Cataract surgical coverage was 96.7%. ‘Need not felt’ (36.6%) and ‘cost’ (31.7%) were the most common barriers for cataract surgery. CONCLUSION: Prevalence of blindness is showing declining trend in urban India. Cataract remains a major cause of blindness followed by posterior segment disorders. Social marketing, and referral linkages between community and service providers were planned after this survey.